Non-Enzymatic Methylglyoxal Formation From glucose Metabolites and Generation of Superoxide Anion Radical During Methylglyoxal-Dependent Cross-Links Reaction - V.Z., Lankin; O.I., Shadyro; K.B., Shumaev; A.K., Tikhaze; A.A., Sladkova (Journal of Antioxidant Activity, 2019)
The paper explores the formation of a-oxoaldehydes during the interaction of glucose metabolites with hydroxyl or alkoxyl radicals. Hydroxyl radicals were generated under radiolysis of aqueous solutions, and alkoxyl radicals (t-BuO) were obtained in the model system tert-butyl hydroperoxide/Fe2+. High-performance liquid chromatography revealed that methylglyoxal was one of the organic products resulting from t-BuO-induced transformations of fructose-1,6-bisphosphate under hypoxic conditions. The interaction of lysine and methylglyoxal one of the main targets of a-oxoaldehydes in proteins was also studied. As chemiluminescence and EPR spectroscopy demonstrated, this reaction generates a methylglyoxal anion radical, a cation-radical of methylglyoxal dialkylamine and a superoxide anion radical. EPR signal of methylglyoxal-derived free radicals was observed in hypoxia, whereas only the trace amounts of these free radicals were recorded in the aerated reaction medium.
Keywords: free radicals; organic hydroperoxides; α-oxoaldehydes; glucose metabolites.